Analysing the state of student participation in two Eco-Schools using Engeström’s Second Generation Activity Systems Model - Schröder, Laura-Marie U.; Wals, Arjen E. J.; van Koppen, C. S. A. (Kris) (Environmental Education Research, 2020)
This research investigates the state of student participation in the Eco-Schools programme in two selected secondary schools located in Spain and the Netherlands. The focus is on understanding the levers of student participation and of the factors leading to a whole-school approach. Engeström’s Second Generation Activity Systems Model is used as an analytical framework. The study also reflects on the merits and shortcomings of this framework. The analysis of the two cases revealed contradictions in the intended effect of the Eco-School programme on fostering student-led change towards sustainability and a whole-school approach. The research suggests that student participation in Eco-School programme can be fostered by using an activity-based ‘whole institution’ approach that interlinks a reflective and action-based procedure, by adapting the students’ learning environment according to their needs and capabilities, by providing for close teacher guidance in Eco-School activities and establishing good student-teacher-relationships, and, finally, by incorporating the Eco-School programme into the school’s overall educational framework.
Publisher: Routledge _eprint: https://doi.org/10.1080/13504622.2020.1779186
Keywords: Cultural-Historical-Activity-Theory (CHAT); Eco-Schools programme; Education for Sustainable Development (ESD); student-led change